Teachersâ Perceptions on the Process of Genre-Based Approach in Teaching Writing - Ardiansah, Dian (EDUCARE, 2017)
ABSTRACT: Despite the process of writing, which needs times to generate the ideas, plan what they are going to write, what they want to share, and their weaknesses in writing, is made the implementation of genre based in writing activity can be one of teaching methods which can be used by the teachers in order to improve studentsâ proficiency and their interesting in English writing. Furthermore, the actual implementation of genre-based approach in teaching writing also helps students to operate within writing rules, knowing different style in writing, and producing their good writing. This study was employed descriptive qualitative design since this study focuses on which is the implementing of genre-based approach in teaching writing covering the perspectives, problems, and solutions toward the implementation of genre-based approach in teaching writing. The data were obtained by using two techniques, namely open ended questionnaire and semi-structured interview. The participants of the study are two teachers at one of private Islamic senior high school in Kawali, Ciamis, West Java, Indonesia. The data were collected and analyzed using model of triangulation process by M.B. Miles & A.M. Huberman (1994) consisting of data reduction, data display, and conclusion. The findings showed that the English teachers faced several problems in implementing an approach in teaching writing based a genre. They felt difficult to assess a big number of students with several domains in limited creativity in their thinking. The main suggestion that the teachers are suggested to apply an approach based on genre in teaching English, not only in teaching writing but in teaching listening, reading, and speaking since this method can improve studentsâ proficiency in learning English as a foreign language.KEY WORDS: Teaching Writing; Implementation Process; Genre-Based Approach; English Teachers; Secondary School Students.About the Author: Dian Ardiansah is a Postgraduate Student at the SPs UPI (School of Postgraduate, Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. For academic interests, the author is able to be contacted via e-mail at: ardhy079@gmail.comSuggested Citation: Ardiansah, Dian. (2017). âTeachersâ Perceptions on the Process of Genre-Based Approach in Teaching Writingâ in EDUCARE: International Journal for Educational Studies, Volume 10(1), August, pp.33-42. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Article Timeline: Accepted (September 29, 2016); Revised (March 2, 2017); and Published (August 30, 2017).